A preliminary study of the properties of the essential oil from the bulbs of Allium sativum Linn. - Nicolas, William F.
Essential oil from fresh bulbs of garlic, Allium sativum Linn. (Fam. Liliaceae) was extracted by steam distillation using the Clavenger apparatus, and analyzed for its physical and chemical properties. Chemical analyses done involved thin layer chromatography in various solvent systems, gas chromatography and ultraviolet spectroscopy.